Growth and productivity in agriculture and agribusiness : evaluative lessons from World Bank Group experience (World Bank, 2011)
The report assesses the World Bank Group?s support for growth and productivity in the agriculture sector. Enhancing agricultural growth and productivity is essential to meeting the worldwide demand for food and to reducing poverty, particularly in the poorest developing countries. Between 1998 and 2008, the period covered by this evaluation, the World Bank Group (WBG) provided 23.7 billion in financing for agriculture and agribusiness in 108 countries (roughly 8 percent of total WBG financing), spanning areas from irrigation and marketing to research and extension. However, this was a time of